The genre of ballet portrait in the historical and cultural heritage of artists "Art World" //El género de retrato de ballet en el patrimonio histórico y cultural de los artistas "Mundo del Arte" - Portnova, Tatiana V. (Revista de la Universidad del Zulia, 2020)
Abstract The author focuses on the features of the artistic embodiment of the actor’s images, based on the creative concept and aesthetic vision of a particular artist, a member of the Creative Union of the World of Art. The article reveals the innovative use of the retrospection technique in their work, highlights the main elements of genre modification. The study is based on the material of individual groups of images belonging to different artists, but formed according to a similar typology, thus, the urgent need for a closer and more versatile view of the theater portrait as one of the key forms in the genre system of the period under consideration becomes obvious. A system analysis of the genre is used, studying the set of artistic tools that artists use to most adequately implement their ideas. An analysis of the main components of the artistic structure reveals the genre features of the ballet portrait as an important vector of the individual search for artists of the “World of Art” association. Resumen El autor se centra en las características de la encarnación artística de las imágenes de ballet, basándose en el concepto creativo y la visión estética de un artista en particular, miembro de la Unión Creativa del Mundo del Arte. El artículo revela el uso innovador de la técnica de la retrospección en su trabajo, destaca los principales elementos de la modificación de género. El estudio se basa en el material de grupos individuales de imágenes pertenecientes a diferentes artistas, pero conformadas según una tipología similar, de ahí la urgente necesidad de una visión más cercana y versátil del retrato teatral como una de las formas clave del género. Se utiliza un sistema de análisis del género, estudiando el conjunto de herramientas artísticas que utilizan los artistas para implementar de la manera más adecuada sus ideas. Un análisis de los principales componentes de la estructura artística revela los rasgos de género del retrato de ballet como un vector importante de la búsqueda individual de artistas de la asociación “Mundo del Arte”.